Constitutive Modeling of the Flow Stress Behavior for the Hot Deformation of Cu-15Ni-8Sn Alloys - Niu, Dongxin; Zhao, Chao; Li, Daoxi; Wang, Zhi; Luo, Zongqiang; Zhang, Weiwen (Frontiers in Materials, 2020)
Three constitutive models, strain-compensated Arrhenius model, modified Johnson–Cook (JC) model and modified Zerilli–Armstrong (ZA) model, were established for the hot-deformed Cu-15Ni-8Sn alloy based on hot compression tests. By introducing average absolute relative error (AARE), correlation coefficient (R) and relative error, the prediction accuracy of these three models was assessed. The results indicate that strain-compensated Arrhenius model has the highest accuracy at describing the flow stress behavior of the studied alloy, followed by modified JC model and modified ZA model. Moreover, the strain-compensated Arrhenius model established in this work has a great practicability in the hot extrusion simulation of Cu-15Ni-8Sn alloys, which can be implemented as the theoretical basis for optimizing hot deformation parameters in industrial production of the Cu-15Ni-8Sn alloys.